EDUKASI TENTANG KESEHATAN REPRODUKSI PADA REMAJA AWAL DI SD NEGERI 2 JABON MOJOANYAR KABUPATEN MOJOKERTO - Elyana Mafticha; Siti Rachmah; Dwi Helynarti Syurandhari (Jurnal Pengabdian Masyarakat, 2024)
Reproductive health promotion is still not free to convey, and is considered taboo, so some formal school-level institutions are still hesitant to carry out reproductive health counseling for their students. Adolescents are a group that has a high vulnerability to reproductive health problems. The purpose of this activity as a form of community service carried out by the Lecturer Team and students of Majapahit College of Health Sciences is as an effort to educate students at SD Negeri 2 Jabon Mojoanyar Mojokerto Regency about reproductive health education in early adolescents. Education by lectures, discussions and counseling demonstration. The activity which was carried out for one month was able to improve students' understanding of reproductive health in early adolescents and how to overcome if they experience problems related to reproductive health. This activity is expected to be a concern, especially in the world of education, increasing education on reproductive health promotion programs Keywords: reproductive health, early adolescence, health promotion